Nutritional strategies for Nile tilapia: protein and carbohydrate balances in saline-alkaline aquaculture - Wei Liu; Erchao Li; Chang Xu; Liqiao Chen; Xiaodan Wang (Journal of Animal Science and Biotechnology)
Abstract Background The development of saline-alkaline water aquaculture is an important part of the development of the global food supply. However, there is still limited knowledge about nutritional strategies for aquaculture in saline-alkaline water, including essential nutrients such as proteins and carbohydrates. In this study, our objective was to elucidate the role of different protein-to-carbohydrate ratios in the adaptation of Nile tilapia (Oreochromis niloticus) to salinity-alkalinity stress. Results Fish were fed three isoenergetic (16.5 kJ/g) and isolipidic (60 g/kg) diets with different protein-to-carbohydrate ratios (27% protein and 35% carbohydrate; 35% protein and 25% carbohydrate; 42% protein and 15% carbohydrate) for 50 d. Nile tilapia (0.44 ± 0.03 g) were exposed to both freshwater (salinity: 0.2 PSU; alkalinity: 0.5 g/L NaHCO₃) and saline-alkaline water (salinity: 16.0 PSU; alkalinity: 3.0 g/L NaHCO₃) to observe changes in growth performance, whole-body composition, and antioxidant capacity. To further elucidate the role of protein-to-carbohydrate ratios, we performed gut microbiota and transcriptomic analyses. The results revealed that salinity-alkalinity stress induced oxidative stress, damaged the gill tissue structure, caused hepatocyte cytoplasmic vacuolation, increased the energy demand and the abundance of intestinal pathogens, and ultimately inhibited the growth of tilapia. A diet containing 27% protein and 35% carbohydrate significantly alleviated oxidative stress in tilapia, increased their crude protein content, and ultimately significantly improved the growth performance. Further analyses of the intestinal microbiota and transcriptomics revealed that a diet containing 27% protein and 35% carbohydrate increased the abundance of probiotics in the gut and upregulated energy metabolism pathways related to glucose metabolism. Conclusions The diet containing 27% protein and 35% carbohydrate increased the abundance of probiotics in the gut, promoted energy metabolism, and improved the growth performance of tilapia under long-term salinity-alkalinity stress. This study evaluated the impact of protein and carbohydrate levels on the growth of tilapia in saline-alkaline water, offering theoretical support for the development of the saline-alkaline water feed industry. This study also highlighted the crucial role of saline-alkaline water aquaculture in global food security and nutritional supply.